2013
DOI: 10.1089/end.2013.0189
|View full text |Cite
|
Sign up to set email alerts
|

Recipient Graft Failure or Death Impact on Living Kidney Donor Quality of Life Based on the Living Organ Donor Network Database

Abstract: Donor QoL declines after recipient death but recovers with time. Graft failure resulted in decreased QoL without recovery. The LODN database identifies factors affecting LKD QoL and provides a model for a national registry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Our data also showed an association between fatigue and recipient death. This is in line with previous research which has demonstrated that recipient death can produce a feeling of guilt [ 32 ] and influence LKD’s well-being [ 10 , 33 ]. In addition, there were donors who had experienced a negative change in the relationship with the recipient, which may be disappointing.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our data also showed an association between fatigue and recipient death. This is in line with previous research which has demonstrated that recipient death can produce a feeling of guilt [ 32 ] and influence LKD’s well-being [ 10 , 33 ]. In addition, there were donors who had experienced a negative change in the relationship with the recipient, which may be disappointing.…”
Section: Discussionsupporting
confidence: 92%
“…Unfortunately, this aspect could not be addressed in the present study but paying attention to those who donate to a recipient at high-risk may be appropriate. Adverse outcomes for the recipient have also been found to be associated with adverse psychosocial outcomes for LKD in previous studies [ 10 , 32 , 33 ]. However, for the donor population as a whole, the donors in our study did not blame themselves if the result was poor.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The multivariable analysis demonstrated that recent recipient death predicted lower donor PCS and MCS scores. A recent study identified an intermittent dip in HRQOL for living kidney donors whose recipient died [42]. Similar to our findings, those recipients mostly recovered back to baseline.…”
Section: Discussionsupporting
confidence: 89%
“…Perhaps the main finding of our study is that recipients’ death almost tripled the risk of the donor becoming lost to follow‐up. Recipient's death has been related to negative outcomes in donors such as reduced motivation and activity, guilt and regretting donation . Less severe complications such as recipient re‐hospitalizations have been also related to the increase of psychological distress in donors .…”
Section: Discussionmentioning
confidence: 99%